Virus-like Particles as Antiviral Vaccine: Mechanism, Design, and Application - Zhang, Lei; Xu, Wen; Ma, Xi; Sun, XiaoJing; Fan, JinBo; Wang, Yang (Biotechnology and bioprocess engineering, 2023)
Virus-like particles (VLPs) are viral structural protein that are noninfectious as they do not contain viral genetic materials. They are safe and effective immune stimulators and play important roles in vaccine development because of their intrinsic immunogenicity to induce cellular and humoral immune responses. In the design of antiviral vaccine, VLPs based vaccines are appealing multifunctional candidates with the advantages such as self-assembling nanoscaled structures, repetitive surface epitopes, ease of genetic and chemical modifications, versatility as antigen presenting platforms, intrinsic immunogenicity, higher safety profile in comparison with live-attenuated vaccines and inactivated vaccines. In this review, we discuss the mechanism of VLPs vaccine inducing cellular and humoral immune responses. We outline the impact of size, shape, surface charge, antigen presentation, genetic and chemical modification, and expression systems when constructing effective VLPs based vaccines. Recent applications of antiviral VLPs vaccines and their clinical trials are summarized.